A comprehensive comparative study among the newly developed Pure Brew method and classical ones for filter coffee production. (1st February 2023) - Santanatoglia, Agnese; Caprioli, Giovanni; Cespi, Marco; Ciarlantini, Dario; Cognigni, Luca; Fioretti, Lauro; Maggi, Filippo; Mustafa, Ahmed M.; Nzekoue, Franks; Vittori, Sauro
Abstract: Pure Brew represents a real innovation because it allows one to obtain a fast-filter coffee with an espresso machine without the need for the barista to purchase additional equipment. This study investigated the difference between Pure Brew, French Press, V60 and AeroPress in terms of physical and chemical characteristics, extraction yields, volatile compounds by GC-MS and bioactive molecules by UHPLC-MS of resulting coffee, studying also powder particle size. Finally, main results showed that Pure Brew is comparable to other methods available on the market, but also showed the highest levels of caffeine (598.28 ± 8.84 and 556.13 ± 1.22 μg/mL) and total bioactive compounds (1726.8 ± 22.4 and 1407.89 ± 9.53 μg/mL) in medium and dark roasted coffee, compared to the other brewing methods. Pure Brew also displayed the most positive results in extraction yields, it falls into the ideal extraction percentage (18–22%) at the three different degrees of roasting, versus the other brewing methods. At the light roast, for Pure Brew were discovered the most olfactometrically impactful molecules of the study at GC-MS, 5-Methyl 2-furancarboxaldehyde, Furfural, and 2-Furanmethanol, connected with positive remarks, associated with almond and sweet. Highlights: Filter coffee: V60, French Press and Aeropress compared with the Pure Brew system. Effect of different filter coffee extraction methods using light, medium and dark roasted coffee. Pure Brew showed similar or better than other filter coffee methods. Pure Brew requires lower preparation time and a simpler machinery.